A new species of Brasineura Silva-Neto & García Aldrete (Psocodea, ‘Psocoptera’, Ptiloneuridae), with comments on morphological variation in B. troglophilica and a revised generic diagnosis - Neto, Alberto Moreira Da Silva; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2016)
Brasineura serranortensis sp. n. is here described and illustrated. This is the third known species of Brasineura and differs from the other species in the genus in phallosome, hypandrium and paraproct structure. Comments on variation in fore wing venation, and new records for B. troglophilica are included. A revised generic diagnosis is also presented.